WAVES FORMATION IN CAPILLARY VOLUMES OF MAGNETIC FLUID - A.Ya. Simonovskii; N.A. Shatalov; P.A. Assorov; A.R. Zakinyan (Applied Engineering Letters, 2022)
This paper presents experimental studies of the influence of an alternating magnetic field on the separation of magnetic liquid droplets from a capillary hole. The formation of waves on the surface of capillary volumes of a magnetic fluid flowing out of a capillary hole in a horizontal non-magnetic plate under the action of gravity in external alternating magnetic field is detected. Spherical, dumbbell-shaped, jet-shaped, and comb-shaped droplet geometries were observed. It is established that the shape of the waves formed could vary from waves running and standing on the surface of a growing drop to bending oscillations of a vertical fluid jet. The magnetic field parameters at which different instability patterns are observed were determined.